Effects of Clostridium perfringens enterotoxin on metabolic indexes of everted rat ileal sacs. - McDonel, J L (1975)
Everted sacs of rat ileum were incubated in Ringer phosphate solution while oxygen uptake, glucose uptake, and lactate production were determined. Sacs treated with Clostridium perfringens enterotoxin, in the form of crude cell-free extract and purified protein, consumed significantly less oxygen than untreated sacs. However, the toxin-treated sacs took up glucose and produced lactate at levels that were not significantly different than those observed in controls. We conclude that oxidative metabolism is inhibited by the action of the toxin, whereas conversion of glucose to lactate via glycolysis seems unaffected